Analysis of ideation, appraisal, and information flow in language learning histories - Rodrigues-Júnior, Adail Sebastião (2010)
Over the last few years, Language Learning Histories have revealed aspects of foreign language acquisition processes that neither ordinary observation nor emic research has been able to capture. This is true because the multiple aspects of the learning language system are not easily perceived by observation techniques only, especially those related to students’ awareness of the process they are part of. Language Learning Histories have much to say about students’ feelings, wishes, and standpoints, and these histories have undoubtedly struck a chord with foreign language students and the field experiences they have had worldwide. The importance of Language Learning Histories to Second/Foreign Language Acquisition Research has motivated me to understand it as a genre with typical as well as distinct discursive features, when compared to the narratives Labov (1972) investigated. This paper thus aims to analyze Language Learning Histories from a genre-based perspective, by using Systemic-Functional Linguistics genre theory to pinpoint some functional stages that usually appear in the Language Learning Histories studied. The data are thirty seven transcripts of Language Learning Histories from Brazilian students available at AMFALE Project homepage. Following Halliday & Hasan’s (1985) position that every context is in the text, this ongoing research adopts Martin & Rose’s (2003) textual approach to both categorize the Language Learning Histories and depict a major picture of this specific genre. The results have demonstrated that a distinguishing feature of this genre, which pervades most of the data analyzed, is the fact that Language Learning Histories present discursive differences in their conclusion, or Coda, in relation to Labov’s categorization.